AC Breakdown Voltage Of Natural Ester Mixed With Iron Oxide For Oil-Immersed Power Transformer Application - Mohd Safwan, Mohamad; Hidayat, Zainuddin; Sharin, Ab Ghani; Imran, Sutan Chairul (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2015)
Nowadays, nanoscale materials are increasingly popular in academic and industrial research. It is expected that the combination of nanoscale materials with other material can contribute more benefits. The use of nanoscale materials often require their dispersion in variety of liquids, to enable them to become part of the liquid product, also known as nanofluids. For example, one of the applications is the nanoparticles dispersed with transformer oil in oil-immersed transformer application. Traditionally, mineral oil is used as dielectric liquid and cooling medium in power transformer. In this paper, dielectric strength of ester oil when mixed with nanoparticles is investigated. For that purpose, AC breakdown voltage test is compliance with ASTM D1816 standard is performed. Statistical analysis and high dimension visualization have been done to analyse and compare the result between fresh ester oil taken from tank and the similar ester oil that mixed with nanoparticles. The results suggest that ester oil mixed with nanoparticles of 0.02 % by volume performs well compared to other samples.